Peningkatan Keterampilan Praktik Pertanian yang Baik Petani Sawit Swadaya di Kabupaten Sambas - Herades Difa Lestari; Nurliza Nurliza; Shenny Oktoriana (Jurnal Ilmu Pertanian Indonesia, 2024)
Good oil palm cultivation contributes to the progress of the national economy by earning foreign exchange and income, creating jobs, and increasing welfare. However, independent palm oil farming has low productivity and quality due to limited knowledge and skills of GAP (Good Agriculture Practices). The research aims to formulate improvements in GAP skills, including technical skills, human skills, and conceptual skills, using skills theory and the concept of sustainability. The research method was descriptive-quantitative with Multidimensional Scaling using the Rap-Palm Oil program on 100 respondents in Sambas Regency, one of the centers of independent oil palm smallholders in West Kalimantan. The results showed that conceptual skills through extension activities are prioritized in improving GAP skills. Therefore, counseling methods through demonstration plots, comparative studies, and field schools can be an effort to improve GAP skills for sustainable management of oil palm farming. Keywords: good agriculture practices, multidimensional scaling, palm oil, skills